Study of XPD Gene Polymorphism in HCV Positive HCC Egyptian Patients - Bothaina Madkour, Ola Mahmouad, Omar M.Sabry, Ahmed R. Mashaal, Mohamed A. El-Refaiy, Rabab Fouad, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Hepatocellular carcinoma (HCC) is one of the most frequently occurring tumorous cells globally, but its pathogenesis is unknown. Xeroderma pigmentosum gene D (XPD) is a critical Repair of DNA gene that has been implicated in protein mutation. Aim: The objectives of this research were to assess the relationship between the XPD gene polymorphism (rs13181) (codon 751, Lys to Gln) and susceptibility to hepatocellular neoplasms, as well as to investigate the relationship between HCV and XPD polymorphisms. Methods: Seventy-nine HCC patients and 63 patients with active HCV infection, and 52 healthy controls were involved. Real-time PCR carried out for genotyping of XPD Lys751Gln (rs 13181). Results: Patients with XPD Lys751Gln AC genotype have a great risk of HCC development (p = 0.01, OR =1.505). Conclusion: Our finding was that XPD Lys751Gln (A/C) polymorphism exhibit a major function in HCC early detection susceptibility in Egyptian patients. It has the potential to be a valuable noninvasive molecular indicator for evaluating the HCC threat.